Characterization of an antibacterial peptide from indian cobra (Naja naja) venom - Sachidananda,M. K. (2007)
Due to the development of antibiotic resistance in microorganisms, antimicrobial peptides from natural sources have attracted attention in recent times. Several antimicrobial peptides have been isolated from a wide range of animal sources, particularly snake venoms. Naja naja venom showed antibacterial as well as direct and indirect hemolytic activities, and an antibacterial peptide was purified through gel permeation and ion exchange chromatography. Its molecular mass was 2491Da, which was determined using Matrix Assisted Laser Desorption/Ionization-Time-of-Flight (MALDI-TOF) mass spectrometry and the amino acids sequence of the N-terminus was DEQSTHGAYVWKL. The purified peptide showed potent antibacterial activity against Gram-negative and Gram-positive bacterial strains like Escherichia coli, Pseudomonas aeruginosa and Vibrio cholerae, and Staphylococcus aureus, Enterococcus faecalis, Streptococcus pneumoniae, Streptococcus pyogenes, Bacillus subtilis, respectively. The most potent activity was towards Gram-negative bacteria. Activity was retained at concentrations as low as 100µg/ml. Minimum inhibitory concentrations (MIC; in mg) of Naja Antibacterial Peptide (NAP) and known antibiotics against Gram-positive and Gram-negative bacteria were determined using microdilution susceptibility test in sterile 96-well microdilution plates. However, the peptide did not show direct or indirect hemolytic activity.